Geburtenbarometer Vienna: Analysing fertility convergence between Vienna and Austria - Krytof Zeman; Tomá Sobotka; Richard Gisser; Maria Winkler-Dworak; Wolfgang Lutz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2011)
Geburtenbarometer Vienna aims to provide an up-to-date monitoring of fertility in Vienna, based on a set of annual and quarterly indicators of fertility rates and regularly published summary reports. This paper gives an overview of the data, methods and indicators used and contrasts main results with the data for other Austrian regions and for the whole country. Throughout much of the 20th century, Vienna recorded fertility rates deep below those in other parts of Austria. Because fertility in Vienna differs markedly between Austrian-born and foreign-born women, our study looks at these fertility differentials and their influence on the overall fertility patterns for Vienna and Austria. Migrant women in Vienna not only had a rapidly increasing share on total births since the mid-1980s and thus contributed to a gradual increase in the absolute number of births in the city, but their higher fertility has also helped to push period fertility rates in Vienna towards the levels recorded in other regions of Austria. Our study brings to light the distinct population dynamics in Vienna, where high childlessness and low fertility are combined with a positive balance between births and deaths and sustained population growth and where the population trends are strongly influenced by the direct and indirect effects of migration. – – Das Geburtenbarometer Wien zielt darauf ab, ein aktuelles Fertilitätsmonitoring für Wien zur Verfügung zu stellen, basierend auf einem Satz jährlicher und vierteljährlicher Fruchtbarkeitsindikatoren und regelmäßigen zusammenfassenden Berichten. Die vorliegende Studie informiert über die verwendeten Daten, Methoden und Indikatoren und kontrastiert die Hauptresultate mit Daten für die anderen österreichischen Regionen und für das ganze Land. Den größten Teil des 20. Jahrhunderts hindurch lag die Fertilität in Wien weit unterhalb jener des übrigen Österreichs. Weil sich die Fruchtbarkeit in Wien deutlich zwischen den in Österreich und den im Ausland geborenen Frauen unterscheidet, werden diese Fertilitätsdifferentiale und ihr Einfluss auf die gesamten Fertilitätsmuster Wiens und Österreichs betrachtet. Zugewanderte Frauen hatten in Wien seit der Mitte der 1980er Jahre nicht nur einen schnell zunehmenden Anteil an den Gesamtgeburten und trugen folglich zu einem allmählichen Anstieg der absoluten Geburtenzahl in der Stadt bei, sondern ihre höheren Fruchtbarkeitsziffern halfen auch, die Periodenfertilitätsraten in Richtung auf die Niveaus zu bringen, die in anderen Regionen Österreichs verzeichnet werden. Die vorliegende Studie veranschaulicht die ausgeprägte Wiener Bevölkerungsdynamik, in der sich eine hohe Kinderlosigkeit und niedrige Fertilität mit einer positiven Bilanz zwischen Geburten und Sterbefällen sowie anhaltendem Bevölkerungszuwachs verbinden und die Bevölkerungstrends stark durch die direkten und indirekten Auswirkungen der Migration beeinflusst werden.
Keywords: 300; Fertility; Vienna; Austria; parity progression ratios; fertility measurement; migrants' fertility; Fertilität; Wien; Österreich; Familienzuwachswahrscheinlichkeiten; Fertilitätsmessung; Fertilität von Migrantinnen; Fertilität; Vergleich; Wien; Österreich